Continuing Formal Education for Nurses in Ghana: The Perception of Non-Professional Nurses - Edith Biamah Agyepong (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2017)
Introduction:Continuing education is essential to the growth of the nursing profession due to the dynamic environment of the health industry. The study sought to explore the perceptions of non – professional nurses regarding continuing education. Methods:The qualitative descriptive design was employed and the purposive sampling technique used to recruit twenty - three non – professional nurses from Pantang Hospital in the Greater Accra Region. Thematic content analysis was used in analyzing the data. Results:The finding of the study showed that non – professional nurses have positive perceptions about continuing education. They believe that engaging in continuing education would improve their care giving skills in order to provide quality care to their clients. Conclusions: The study recommends that non-professional nurses with basic qualifications in the nursing profession should be encouraged to pursue continuing education.